Identification of potential inhibitors of omicron variant of SARS-Cov-2 RBD based virtual screening, MD simulation, and DFT - Lü, Xudong; Feng, Cuiyue; Lü, Ruijie; Wei, Xiyu; Fan, Shuai; Yan, Maocai; Zhu, Xiandui; Zhang, Zhifei; Yang, Zhaoyong (Frontiers in Chemistry, 2022)
The emergence of the SARS-CoV-2 Omicron variant of concern (VOC; B.1.1.529) resulted in a new peak of the COVID-19 pandemic. This called for the development of effective therapeutics against the Omicron variant of concern (VOC). Studies have identified the receptor binding domain (RBD) of the spike protein, which is responsible for the recognition and binding of human ACE2 receptor protein, as a potential drug target. Numerous mutations in the RBD of the S-protein are thought to enhance the binding strength of the Omicron VOC to host proteins. In this study, we utilized bioinformatic analyses to screen for potential therapeutic compounds targeting the omicron VOC. Overall, 92,699 compounds were screened from different libraries based on the RBD of the S-protein through docking and binding free energy analysis, yielding only the top 5 best hits. We used dynamic simulation trajectory analysis and binding free energy decomposition to determine the inhibitory mechanism of candidate molecules by focusing on their interactions with recognized residues on the RBD. ADMET prediction and DFT calculations were conducted to determine the pharmacokinetic parameters and precise chemical properties of the identified molecules. Our findings indicated that the molecular properties of the identified molecules and their ability to interfere with recognition of human ACE2 receptors by the RBD suggest that they are potential therapeutic agents for the control of SARS-CoV-2 Omicron VOC.